Audience Reception Related to Freedom of Life Partner in Aladdin Film - Novita Ika Purnamasari (Ikatan Sarjana Komunikasi Indonesia, 2020)
Aladdin's film, tells not only about romance but also family problem communication, specially differences of opinion and perspective of parents in choosing their child's life partner. Not only is the problem found in the movie but also in everyday life. Parental demands for a child's life partner have an impact: loss of freedom to choose the desired life partner. As a result, there arise disappointment, conflicts, and feelings of depression to unwillingness to get married. This condition is exacerbated by the influence of family’s cultural background or certain restrictions. Using the Stuart Hall reception analysis model, this study involves four parents who have watched Aladdin's film with different backgrounds, cultures and experiences, and have teenagers entering adulthood. The results showed that the era of media and information openness has had an impact on changing parents' communication patterns to be more open, dynamic and aware of children's desires. Three parents are in a negotiating position with no emphasis on cultural background but religious similarity, and one parent is in a dominated position, freeing the child to determine a life partner without any criteria. Each parent captures the message of Aladdin's film by linking it to family experiences and personal knowledge.